Skin Lightening as Appearance Management Procedure: The Zimbabwean Situation - Lucia, Sithole; Sithole, Fungai Kumbulani (World Journal of Business and Management, 2024)
The desire for lighter skin as a sign of class and wealth has trickled down many generations to now deeply impact the darker coloured races making skin whitening almost an outbreak. There is a general myth that light skinned women are more attractive to men, get employed faster and have sound effect. Beauty products today have soared in the Zimbabwean market due to the growing demand. However, what is not promoted is the harm that a lot of these products can do in the medium to long term application. Eating healthy and exercising can improve the skin’s texture. Application of sunscreen and intake of at least two litres of water per day are some of the natural ways of having great skin rather than applying skin bleaching creams. Some cost-effective easy homemade skin lightening remedies which will brighten and whiten the skin and impart it with a natural glow can be used and these can manifest good results. However, due to colonial mind-sets, people always believe that white is better and beautiful hence the use of skin lightening products, consequently there is need for change of mind-set.